2016
DOI: 10.1590/1414-431x20165272
|View full text |Cite
|
Sign up to set email alerts
|

Obesity inversely correlates with prostate-specific antigen levels in a population with normal screening results of prostate cancer in northwestern China

Abstract: Serum prostate-specific antigen (PSA) is a diagnostic biomarker of prostate cancer and is possibly associated with obesity. This study aimed to explore the relationships between obesity indicators [body mass index (BMI) and waist circumference (WC)] with PSA in Chinese men. A cross-sectional study of men aged 30-85 years undergoing prostate cancer screening was conducted from August 2008 to July 2013 in Xi'an, China. Data were obtained from clinical reports, condition was recorded based on self-report includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
3
16
1
Order By: Relevance
“…The PheWAS performed on the SNP associations in this study's BMI cohort identified strong 599 associations of elevated PSA levels with variants in FTO, and indicates that the number of minor 600 alleles of these variants is predictive of elevated PSA. This finding is in contradiction to the reports 601 (Bañez et al 2007;Oh et al 2013;Zhang et al 2016;Bonn et al 2016) indicating an inverse 602 relationship between PSA levels and BMI. However, serum levels of PSA may be elevated due to 603 reasons other than prostatic malignancy.…”
Section: Phewas Of Healthy Nevada Bmi and Obesity 592mentioning
confidence: 64%
“…The PheWAS performed on the SNP associations in this study's BMI cohort identified strong 599 associations of elevated PSA levels with variants in FTO, and indicates that the number of minor 600 alleles of these variants is predictive of elevated PSA. This finding is in contradiction to the reports 601 (Bañez et al 2007;Oh et al 2013;Zhang et al 2016;Bonn et al 2016) indicating an inverse 602 relationship between PSA levels and BMI. However, serum levels of PSA may be elevated due to 603 reasons other than prostatic malignancy.…”
Section: Phewas Of Healthy Nevada Bmi and Obesity 592mentioning
confidence: 64%
“…Measures were made at the end of normal expiration with special attention paid to ensure the tape was positioned perpendicular to the long axis of the body and parallel to the oor. A series of four measurements were taken by a single, trained researcher from the right side at the following anatomical locations: i) superior border of the iliac crest, ii) midpoint between the iliac crest and the lowest rib, iii) umbilicus, and iv) minimal waist (18). Waist-to-hip ratio (WHtR) was calculated as WC in centimeters divided by height in centimeters and multiply by a hundred (percentage, %).…”
Section: Determination Of Obesity Factorsmentioning
confidence: 99%
“…Prostate cancer is top on the list among causes of cancer-related deaths in men and ranks as the second most common cancer after lung cancer the world over [1]. In Nigeria, there is a gradual trend of rising prostate cancer cases which is attributable to increasing urbanization and changing dietary habit as well as the increased awareness towards the use of health facilities leading to more cases being documented.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) has been linked with aggressive prostate cancer by some studies but its association still requires to be properly established as previous studies have disputed a clear pattern of relationship [2]. Some studies suggest that the effect of BMI on serum prostatespecific antigen levels is inversely related meaning that in obesity or high BMI there is decreased concentration of PSA [1,2]. It is on this premise therefore that some investigators think that obesity, as evidenced by high BMI, might reduce the sensitivity of screening for prostate cancer with prostate-specific antigen (PSA) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation